The potential value of exosomes as adjuvants for novel biologic local anesthetics - Zhang, Yunmeng; Feng, Shangzhi; Cheng, Xin; Lou, Kecheng; Liu, Xin; Zhuo, Ming; Chen, Li; Ye, Junming (Frontiers in Pharmacology, 2023)
The side effects of anesthetic drugs are a key preoperative concern for anesthesiologists. Anesthetic drugs used for general anesthesia and regional blocks are associated with a potential risk of systemic toxicity. This prompted the use of anesthetic adjuvants to ameliorate these side effects and improve clinical outcomes. However, the adverse effects of anesthetic adjuvants, such as neurotoxicity and gastrointestinal reactions, have raised concerns about their clinical use. Therefore, the development of relatively safe anesthetic adjuvants with fewer side effects is an important area for future anesthetic drug research. Exosomes, which contain multiple vesicles with genetic information, can be released by living cells with regenerative and specific effects. Exosomes released by specific cell types have been found to have similar effects as many local anesthetic adjuvants. Due to their biological activity, carrier efficacy, and ability to repair damaged tissues, exosomes may have a better efficacy and safety profile than the currently used anesthetic adjuvants. In this article, we summarize the contemporary literature about local anesthetic adjuvants and highlight their potential side effects, while discussing the potential of exosomes as novel local anesthetic adjuvant drugs.